NEW AND CRITICAL MALESIAN PLANTS VII * - A. J. G. H. KOSTERMANS (Research Center for Biology, 1965)
1. Anacardiaceao: Mangifera caesia Jack is combined with M. kemanga Bl. and 3 varieties are recognized: caesia, kemanga and wanji.2. Newly described are: M. pajang and M. torquenda.3. Lepidadenia seloang Miquel represents: Phoebe declinwta Bl.4. New Lauraceae: Beilschmiedia glabra, B. dictyoneura, B. bangkae, B. raontanoides, B. rivularis; Endiandra ochracea, E. magnilimba.5. In Meliaceae are newly described: Aphanamixis reticulosa, Lansium pedicellatum and L. sepalinum.6. Sterculia minahassae Kds. is referred to Firmiana. F. philippinensis Kosterm. is reduced to synonymy.